The Orphan Choir - Hannah, Sophie, 1971- (Picador, 2014)
"Louise Beeston is haunted... Louise has no reason left to stay in the city. She can't see her son, Joseph, who is away at boarding school where he performs in a prestigious boys' choir. And her troublesome neighbor has begun blasting choral music all hours of the night. And to make matters worse, she's the only one who can hear it. Hoping to find some peace, Louise convinces her husband, David, to buy them a country house in an idyllic, sun-dappled community called Swallowfield. But it seems that the haunting melodies of the choir have followed her there. Could it be that her city neighbor has trailed her to Swallowfield, just to play an elaborate, malicious prank? Is there really a ghostly chorus playing outside her door? And why won't they stop? Growing desperate, she begins to worry about her mental health. Against the pleas and growing disquiet of her husband, Louise starts to suspect that this sinister choir is not only real, but a warning. But of what? And how can it be, when no one else can hear it? In The Orphan Choir, Sophie Hannah brings us along on a darkly suspenseful investigation of obsession, loss, and the malevolent forces that threaten to break apart a loving family. - The Orphan Choir was a major bestseller in the U.K. when it published in June 2013, outselling Hannah's immensely popular Zailer and Waterhouse series. - For fans of Shirley Jackson and Stephen King "--